2016
DOI: 10.1177/1077559516659937
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Functioning and Stress Reactivity in Maltreating Parents and At-Risk Adults

Abstract: We reviewed and meta-analyzed 10 studies (N = 492) that examined the association between (risk for) child maltreatment perpetration and basal autonomic activity, and 10 studies (N = 471) that examined the association between (risk for) child maltreatment and autonomic stress reactivity. We hypothesized that maltreating parents/at-risk adults would show higher basal levels of heart rate (HR) and skin conductance (SC) and lower levels of HR variability (HRV) and would show greater HR and SC stress reactivity, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…The total sample sizes varied from somewhat <500 to over 8,500, but was not always reported. Effect sizes ranged between d = −.10 (for parental autonomic nervous system reactivity, Reijman et al, ) and d = .69 (for parental insecure attachment, Lo et al, ), indicating a broad range of meta‐analytic effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total sample sizes varied from somewhat <500 to over 8,500, but was not always reported. Effect sizes ranged between d = −.10 (for parental autonomic nervous system reactivity, Reijman et al, ) and d = .69 (for parental insecure attachment, Lo et al, ), indicating a broad range of meta‐analytic effects.…”
Section: Resultsmentioning
confidence: 99%
“…A long-standing idea is that the neurophysiology of perpetrating parents is dysregulated, which would make them constitutionally more liable to become abusive. Neural reactivity (Rilling & Young, 2014), as well as autonomic and sympathetic nervous system responses, prepares the individual organism for action to cope with stress, but if the balance between the sympathetic and parasympathetic systems is dysregulated, over-or underreactivity to stressful stimuli such as infant crying might result in harsh parenting or neglect (Reijman et al, 2016). As context factors, single parenthood, lack of social support, and low socioeconomic status have been associated with increased risk for child maltreatment (Stith et al, 2009).…”
Section: How Prevalent Is Child Maltreatment?mentioning
confidence: 99%
“…In addition, Gonzalez et al (2012) found that greater diurnal cortisol secretion (indicated by a larger area under the curve (AUCg) value) mediated the relation between early-life trauma and lower maternal sensitivity. Thus, both higher basal cortisol levels (i.e., diurnal cortisol secretion) and blunted reactivity may indicate a pattern of cortisol dysregulation that acts as a mechanism linking adversity to maladaptive caregiving (Reijman et al, 2016). …”
Section: Cortisol As a Possible Link Between Maternal Adversity And Mmentioning
confidence: 99%
“…Reijman and her colleagues reported significantly lower levels of alpha-amylase, a marker of autonomic nervous system activity, in a clinical sample that included both abusive and neglectful mothers [35], a pattern that has held up across several studies [36]. Childhood poverty, too, has been linked to distinctive responses to infant crying.…”
Section: Adult Responses To Infant Cryingmentioning
confidence: 99%